Human modeling for bio-inspired robotics : mechanical engineering in assistive technologies - Ueda, Jun (Professor of mechanical engineering); Kurita, Yuichi (Academic Press is an imprint of Elsevier, 2017)
This book presents the most cutting-edge research outcomes in the area of mechanical and control aspects of human functions for macro-scale (human size) applications. Intended to provide researchers both in academia and industry with key content on which to base their developments, this book is organized and written by senior experts in their fields. - Resumé vydavatel
Keywords: biomechanika; robotika; biomechanics; robotics; interakce člověk-robot; kolektivní monografie; elektronické knihy; collective monographs; electronic books